Screening of inhibitors for remediation of asphaltene deposits: Experimental and modeling study - Mehdi Madhi; Riyaz Kharrat; Touba Hamoule (Petroleum, 2018)
One of the most severe problems during production from heavy crude oil reservoirs is the formation of asphaltene precipitation and as a result deposition in the tubing, surface facilities and near wellbore region which causes oil production and permeability reduction in addition to rock wettability alteration in the reservoir. So one of the economical ways to prevent such incidents is using the chemicals which are called asphaltene inhibitor.In this study, the influence of three commercial inhibitors, namely; Cetyl Terimethyl Ammonium Bromide (CTAB), Sodium Dodecyl Sulfate (SDS), Triton X-100 and four non-commercial (Benzene, Benzoic Acid, Salicylic Acid, Naphthalene) inhibitors on two Iranian crude oils were investigated. This study extends previous works and contributes toward the better understanding of interactions between asphaltene and inhibitor. Effect of functional groups and structure of inhibitors on asphaltene precipitation were studied and it seems clear that the nature and polarity of asphaltene (structure and amount of impurities presented) has a significant impact on the selection of inhibitors. asphaltene dispersant tests and Core flood tests were designed for evaluation of inhibitors in static and dynamic conditions. The results revealed distinguished mechanisms for asphaltene solubilization/dispersion (such as hydrogen bonding, π–π interaction and acid-base interaction) and influence of additional side group (OH) on inhibition power of inhibitor.During the experiments, it was found that increasing inhibitor concentration may lead to the self-assembly of inhibitor and declining of asphaltene stabilization. So, finding optimum concentration of inhibitor with high efficiency and available at a reasonable price is very important. The results suggest that 600 ppm of CTAB and 300 ppm of SDS were approximately optimum concentrations for the studied crude oils. One of the most important findings that differ from previous studies is the revelation of the mechanism behind the SDS/asphaltene behavior in various concentrations of inhibitor. Effect of chosen inhibitors on asphaltene precipitation and consequently deposition in porous media was studied, and then experimental data were modeled for evaluation of permeability impairment mechanisms. Permeability revived after inhibitor squeezing and cake formation mechanism played an important role in permeability reduction before and after treatment in porous media. The findings can also be applied to prediction of future behavior of reservoirs in oil field scale and evaluation of formation damage in the different period of production if needed any treatment process. Keywords: Asphaltene, Precipitation, Deposition, Inhibitor, Permeability reduction